Effect of cycling position on ventilatory and metabolic variables - Grappe, F.; Candau, R.; Busso, T.; Rouillon, J. D. (International Journal of Sports Medicine, 1998)
Three positions are generally used by cyclists: upright posture (UP), dropped posture (DP) and aero posture (AP). They determine different angles of trunk flexion which could be associated with physiological changes. The purpose of this study was to analyse the effect of these rider positions on ventilatory and metabolic variables. Nine male competitive cyclists (26.3+/-3yrs, mean+/-SD) exercised on a cycle ergometer. Subjects performed three 10 min exercise bouts at 70% VO2max (maximal oxygen uptake, I x min(-1)) in UP, DP and AP, in a randomized order. Each bout was separated by a 5 min active recovery period (50% of VO2max). Ventilatory and gas exchange responses to exercise were averaged every min. Blood lactate concentration ([La]b, mM), blood pH were analysed at the 5th and the 10th min. The ventilation, respiratory exchange ratio, mean inspiratory flow, [La]b and perceived exertion were significantly higher in DP (88.4+/-11.41 x min(-1), 0.96+/-0.05 ml x s(-1), 2.52+/-0.84 Mm and 13.6+/-1.2) than in UP (84.8+/-12.31 x min(-1), 0.94+/-0.05 ml x s(-1), 2.14+/-0.99Mm and 12.1+/-1.5). VO2, tidal volume, carbon dioxide output, respiratory rate, inspiratory duty cycle, heart rate and pH remained unchanged between all riding positions (averaged values for the three positions: 3.09+/-0.0061 x min(-1), 2.34+/-0.0061 x br(-1), 3.01+/-0.041 x min(-1), 37.4+/-0.8 br x min(-1), 0.47+/-0, 162+/-1 beat x min(-1) and 7.38+/-0.015). These results showed that the greater changes in ventilatory and metabolic variables occurred in DP. AP appears to be the more suitable position when the aerodynamic drag becomes predominant.